A primeira via de Tomás e a noção de movimento - Ezídio, Camila de Souza (2015)
Thomas Aquinas builds, in Summa contra Gentiles and in Summa Theologiae, five ways to show the existence of God. Among them, the first one is considered by the philosopher himself as the most manifest, as it comes from a principle that we all realize in the things of the world, movement. This dissertation follows the steps of argumentation which composes the first way in order to understand it itself and in its historic, literary, philosophic, and theological contexts. The search for the foundations of the first way demands that this study goes beyond Thomas Aquinas and reaches Aristotelian philosophy. The analysis of interpretations of commentators about such demonstration of God existence creates new perspectives before arguments built in the medieval period, and raises problems which involve modernity showing that this research comprehends concepts which transit since antiquity to modern period of philosophy history.